PENGARUH MINAT BERWIRAUSAHA MAHASISWA SETELAH MENGAMBIL MATA KULIAH TECHNOPRENEURSHIP - Basrul Abdul Majid; Khalisatun Munawwarah; Hendri Ahmadian; Rahmat Musfikar; Bustami Yusuf (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The purpose of this study was to determine the effect of technopreneurship courses on the entrepreneurial interest of Information Technology Education students. This research was conducted at UIN Ar-Raniry, Faculty of Tarbiyah and Teacher Training. The techniques of data collection used a questionnaire and the data analysis using multiple linear regression. The results showed that there is a positive influence on the variables of learning theory and field practice on the variable of interest in entrepreneurship. The regression coefficient for the learning theory variable or X1 is 0.428, while the regression coefficient for the field practice variable or X2 is 0.331. Therefore the regression equation can be written as follows Y = 12.223 + 0.428 X1 + 0.331 X2. It can be concluded from this research that the implementation of technopreneurship courses explained through the variables of learning theory (X1) and field practice (X2) proved to have a significant effect on the variable of student interest in entrepreneurship (Y). This is because learning theory in technopreneurship courses triggers students to apply it so that it can foster interest in entrepreneurship among information technology education students.